Cover Feature: Surface and Interface Engineering Strategies for MoS2 Towards Electrochemical Hydrogen Evolution (Chem. Asian J. 14/2022). Issue 14 (28th June 2022) - Ding, Yi Ming; Li, Nian Wu; Yuan, Shuai; Yu, Le
Abstract : High‐efficiency electrocatalysts are critical to promote the hydrogen evolution reaction (HER) through electrolysis of water. MoS2 has received great attention as potential electrocatalysts for HER. Surface engineering and interface engineering are effective strategies to enhance HER activity of MoS2 . In this Review, the modification strategies used in recent years to improve the HER activity of MoS2 through surface and interface engineering are summarized. Particularly, the aspects including defects, doping, strain, atomic control and heterostructure are highlighted. More information can be found in the Review by Le Yu et al.